Millennia’s impulsive buying behavior: does positive emotion mediate? - Achmad Choirul; Yessy Artanti (Journal of Economics, Business, and Accountancy Ventura, 2019)
Indonesian buying behavior, especially on generation Y or millennialism, tends to be impulsive, and the rapid development of the retail fashion business allows marketers to learn and formulate the strategy. As a group of people, millennialism is a potential market segment. This study tries to investigate the role of hedonic shopping motives, fashion involvement, and store atmosphere toward positive emotion and impulsive buying. The study also tests the mediating role of positive emotion. Judgmental sampling was employed to collect data from 220 respondents of millennialism in Surabaya, and the relationships were analyzed using path analysis. The study confirms that hedonic shopping motives have no significant effect on impulsive buying, whereas both fashion involvement and store atmosphere have a significant effect on impulsive buying. All hedonic shopping motives, fashion involvement, and store atmosphere have a significant effect on positive emotion. On the contrary, positive emotion has no significant effect on impulsive buying. It also does not mediate the effect of hedonic shopping motivation, fashion involvement, and store atmosphere towards impulsive buying. This study provides novel and useful insights into the complex impulsive buying by millennial by expanding the application of both fashion involvement and store atmosphere for fashion marketers.